AI governance: the IPA case : A Bosch Home Comfort case study - Manoukian, Guillaume (My University, 2023)
This thesis examines the crucial issue of AI governance in companies and addresses the lack of clear governance frameworks that facilitate adopting and maximizing AI benefits. Through a qualitative approach involving ten participants from the Bosch environment (Belgium, Netherlands, Germany, and Portugal), this study investigates the implementation of AI-driven tools and proposes insights for effective governance. Companies should prioritize implementing Intelligent Process Automation by leveraging precise analyses and establishing clear internal guidelines. Moreover, creating dedicated teams, such as a data team, can significantly contribute to automating processes across different departments. This research is built upon existing literature and knowledge in the field while providing unique insights by incorporating an internal perspective within Bosch. In practice, the recommendations from this study can be applied by creating specific teams within the company and emphasizing comprehensive documentation of AI processes and guidelines. Further research could explore developing tailored approaches to suit specific company requirements. It is essential to acknowledge that a limitation of this study is the perpetual evolution of IPA.
Keywords: IPA governance, AI, automation processes, qualitative research, Gioia, Bosch